Il laboratorio nella didattica delle discipline tecnologiche (e scientifiche) (Chimica nella Scuola, 2022)
The article analyses the importance of the laboratory in making teaching effective. The reference is to electronics, but what is reported may also apply to other technological and scientific disciplines and, perhaps, to all school disciplines. The laboratory is important not only for the help it provides in the acquisition of new knowledge, but also because, from a more psychological pointof view, it creates in students a predisposition that encourages the desire to learn.
Keywords: tecnologia; laboratorio; didattica laboratoriale; pensiero riflessivo